Attenuation of the anxiogenic effects of cocaine by 5-HT(1B) autoreceptor stimulation in the Bed Nucleus of the Stria Terminalis of rats - Klein, Adam K. (Psychopharmacology (Berl), 2016)
RATIONALE: Cocaine produces significant aversive/anxiogenic actions whose underlying neurobiology remains unclear. A possible substrate contributing to these actions is the serotonergic (5-HT) pathway projecting from the dorsal raphé (DRN) to regions of the extended amygdala, including the Bed Nucleus of the Stria Terminalis (BNST) which have been implicated in the production of anxiogenic states. OBJECTIVES: The present study examined the contribution of 5-HT signaling within the BNST to the anxiogenic effects of cocaine as measured in a runway model of drug self-administration. METHODS: Male Sprague-Dawley rats were fitted with bilateral infusion cannula aimed at the BNST and then trained to traverse a straight alley once a day for a single 1mg/kg i.v. cocaine infusion delivered upon goal-box entry on each of 16 consecutive days/trials. Intracranial infusions of CP 94,253 (0, 0.25, 0.5, or 1.0μg/side) were administered to inhibit local 5-HT release via activation of 5-HT(1B) autoreceptors. To confirm receptor specificity, the effects of this treatment were then challenged by co-administration of the selective 5-HT(1B) antagonist NAS-181. RESULTS: Intra-BNST infusions of the 5-HT(1B) autoreceptor agonist attenuated the anxiogenic effects of cocaine as reflected by a decrease in runway approach-avoidance conflict behavior. This effect was reversed by the 5-HT(1B) antagonist. Neither start latencies (a measure of the subject’s motivation to seek cocaine) nor spontaneous locomotor activity (an index of motoric capacity) were altered by either treatment. CONCLUSIONS: Inhibition of 5-HT(1B) signaling within the BNST selectively attenuated the anxiogenic effects of cocaine, while leaving unaffected the positive incentive properties of the drug.